2013
DOI: 10.1017/s1751731113001705
|View full text |Cite
|
Sign up to set email alerts
|

Repeated acidosis challenges and live yeast supplementation shape rumen microbiota and fermentations and modulate inflammatory status in sheep

Abstract: This study aimed to investigate the impact of repeated acidosis challenges (ACs) and the effect of live yeast supplementation (Saccharomyces cerevisiae I-1077, SC) on rumen fermentation, microbial ecosystem and inflammatory response. The experimental design involved two groups (SC, n = 6; Control, n = 6) of rumen fistulated wethers that were successively exposed to three ACs of 5 days each, preceded and followed by resting periods (RPs) of 23 days. AC diets consisted of 60% wheat-based concentrate and 40% hay,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
28
1
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(41 citation statements)
references
References 36 publications
(50 reference statements)
3
28
1
4
Order By: Relevance
“…The beneficial effect of S. cerevisiae on fibre fermentation (represented as sugar beet pulp) has been associated with an increase in rumen concentration of cellulolytic bacteria in mixed diets for sheep and buffaloes . Similarly, an increase of rumen concentration of Ruminococcus flavefaciens and Ruminococcus albus has been reported when live yeasts were supplemented to more than 50% concentrate diets for sheep . In contrast, our study showed a limited effect of added yeasts on fermentative activity of rumen bacteria with barley as substrate.…”
Section: Discussionsupporting
confidence: 42%
See 1 more Smart Citation
“…The beneficial effect of S. cerevisiae on fibre fermentation (represented as sugar beet pulp) has been associated with an increase in rumen concentration of cellulolytic bacteria in mixed diets for sheep and buffaloes . Similarly, an increase of rumen concentration of Ruminococcus flavefaciens and Ruminococcus albus has been reported when live yeasts were supplemented to more than 50% concentrate diets for sheep . In contrast, our study showed a limited effect of added yeasts on fermentative activity of rumen bacteria with barley as substrate.…”
Section: Discussionsupporting
confidence: 42%
“…Anyway, the higher VFAs concentration with AY with respect to CT agrees with results from others and supports observed gas production results along the incubation period, although no treatment differences were recorded in molar VFAs proportions, suggesting that the effect of yeasts on fermentation is quantitative rather than qualitative. In this regard, some workers have reported increased proportions of propionate or butyrate in response to yeasts addition, but others did not observe any shift in the fermentation pattern …”
Section: Discussionmentioning
confidence: 96%
“…This may be due to an increase in lactate-utilizing bacteria, Selenomonas ruminantium and Megasphaera elsdenii. These bacteria convert lactate to propionate (Lettat, Martin, Berger, & Nozière, 2012;Silberberg et al, 2013) and have their growth stimulated by the supplementation of yeast (Pinloche et al, 2013).…”
Section: Discussmentioning
confidence: 99%
“…The primary mechanisms of action are to stimulate total rumen bacterial population densities, shift or stabilize the balance of rumen bacterial populations, utilize lactic acid, and reduce the risk for ruminal acidosis, and maintain a low oxygen rumen environment. [78][79][80][81] Newbold and colleagues 78 designed well-controlled experiments to elucidate the mechanisms by which live yeast supplements may increase rumen bacterial population densities. Oxygen utilization by live yeast supplements seems to be an important mechanism improving the growth of rumen bacteria.…”
Section: Probioticsmentioning
confidence: 99%